PENGARUH HIDROGEN PEROKSIDA TERHADAP PRODUKSI HIDROGEN DARI LIMBAH BUAH MELON: Cucumis melo L.) OLEH MIKROBA DIGESTER BIOGAS - KHARISMA, AGUNG DIAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Gas hydrogen is alternative energy which potentially to substitute fossil fuels. Biologycal hidrogen production by dark fermentation is choosen because it is potential as a clean energy source, environmental friendly, and cheaper. Generally, the obstacle of hydrogen production by fermentation on an industrial scale is low energy efficiency, ranging from 0.5 to 2.5 mol H2/mol hexose. Therefore, it is necessary to increase hydrogen production by using hydrogen peroxide (H2O2). The purpose of the study is to determine the effect of H2O2 induction as free radicals agent to the hydrogen and organic acids produced in fermentation by mixed culture of biogas digester. Biohydrogen has been produced using bacth system of fermenter, incubation at 37Â°C, initial pH 7, and 7 days of fermentation. H2O2 induced in the beginning of fermentation with concentration 0,1mM, 0,2mM and 0,4mM. The result of this study is H2O2 inducted with concentration 0,1